Candida auris Pan-Drug-Resistant to Four Classes of Antifungal Agents - Jacobs, Samantha E; Jacobs, Jonathan L; Dennis, Emily K; Taimur, Sarah; Rana, Meenakshi; Patel, Dhruv; Gitman, Melissa; Patel, Gopi; Schaefer, Sarah; Iyer, Kishore; Moon, Jang; Adams, Victoria; et al. (Antimicrobial agents and chemotherapy, 2022)
Candida auris is an urgent antimicrobial resistance threat due to its global emergence, high mortality, and persistent transmissions. Nearly half of C. auris clinical and surveillance cases in the United States are from the New York and New Jersey Metropolitan area. We performed genome, and drug-resistance analysis of C. auris isolates from a patient who underwent multi-visceral transplantation. Whole-genome comparisons of 19 isolates, collected over 72 days, revealed closed similarity (Average Nucleotide Identity > 0.9996; Aligned Percentage > 0.9764) and a distinct subcluster of NY C. auris South Asia Clade I. All isolates had azole-linked resistance in (K143R) and (V704L). Echinocandin resistance first appeared with (S639Y) mutation and then a unique (F635C) mutation. Flucytosine-resistant isolates had mutations in , , and . Two pan-drug-resistant C. auris isolates had uracil phosphoribosyltransferase deletion ( [1 33]) and the elimination of expression, confirmed by a qPCR test developed in this study. Besides mutations, four amphotericin B-resistant isolates showed no distinct nonsynonymous variants suggesting unknown genetic elements driving the resistance. Pan-drug-resistant C. auris isolates were not susceptible to two-drug antifungal combinations tested by checkerboard, Etest, and time-kill methods. The fungal population pattern, discerned from SNP phylogenetic analysis, was consistent with in-hospital or inpatient evolution of C. auris isolates circulating locally and not indicative of a recent introduction from elsewhere. The emergence of pan-drug-resistance to four major classes of antifungals in C. auris is alarming. Patients at high risk for drug-resistant C. auris might require novel therapeutic strategies and targeted pre-and/or posttransplant surveillance.